The Effect of Providing Government-Borne Import Duties Facility on the Growth and Competitiveness of Indonesia's Manufacturing Industry - Hendang Setyo Rukmi; Lukmanulhakim Almamalik (International Journal of Innovation in Enterprise System, 2020)
This research has its aim to study the effect of providing Government-Borne Import Duty facility on the growth and competitiveness of Indonesia's manufacturing industry. The growth of the manufacturing industry is identified with the growth of production, employment, and contribution to state income through taxes. The background of this research is the existence of government's need to find the effect of the provision of exemption from import duties that have been running since 2008 on the ability of companies to produce goods in order to meet consumer needs, competitiveness, employment, and their contribution to state income. The survey was conducted on 110 companies that use this facility in Indonesia. The research applied the statistical method of sign and percentage test with the unit of analysis at the company and target sector, and groups of companies that receive GBID facility with different frequencies. The results show that the provision of the facility significantly increase the growth and competitiveness of Indonesia's manufacturing industry, especially in production growth, the competitiveness of production costs, sales growth, profits, and company productivity. This facility has different effects on companies under different target sectors. More companies under the guidance of Directorate General of MMTEI experinence innovation raising, time-to-market competitiveness, and machine modernization after being given this facility, while more companies under the guidance of Directorate General of CTMI experience production growth, competitiveness raising in production costs, quality, delivery time, sales growth, productivity, human capital, absorption of production labor, and tax payments. The reason related to this case is the existence of difference in production, product standardization, product cycle times, and technological intensity. The results also show that the difference in frequency of facilitation given only affect in rising the competitiveness of the company's products’ price. Related to the nature of production, GBID facility is more suitable to be given to companies that have production plans rather than companies that only do the task based on project or job orders. It is because the companies that have production plan could do the job with more optimal results than those who don’t.